2017
DOI: 10.1101/cshperspect.a025817
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-Based Transport and the Distribution, Tethering, and Organization of Organelles

Abstract: SUMMARY Microtubules provide long tracks along which a broad range of organelles and vesicles are transported by kinesin and dynein motors. Motor protein complexes also tether cargoes to cytoskeletal filaments, helping facilitate their interaction and communication. The generation of biochemically distinct microtubule subpopulations allows subsets of motors to recognize a given microtubule identity, allowing further organization within the cytoplasm. Both transport and tethering are spatiotemporally regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
165
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(178 citation statements)
references
References 70 publications
(75 reference statements)
0
165
0
Order By: Relevance
“…Initially, we found that GFP‐positive puncta, presumably deuterosomes, moved rapidly and were difficult to trace over time (Movie EV1). Impairing microtubule‐dependent intracellular transport by treating the cells with nocodazole (0.5 μg/ml), a microtubule‐destabilizing drug, markedly slowed down the deuterosome motilities. In the presence of nocodazole, we captured 15 cells that initiated their deuterosome biogenesis during the imaging (Fig E and Movie EV2) and 16 cells that already contained deuterosomes from the beginning and showed increased numbers of their deuterosomes over time (Movie EV3).…”
Section: Resultsmentioning
confidence: 99%
“…Initially, we found that GFP‐positive puncta, presumably deuterosomes, moved rapidly and were difficult to trace over time (Movie EV1). Impairing microtubule‐dependent intracellular transport by treating the cells with nocodazole (0.5 μg/ml), a microtubule‐destabilizing drug, markedly slowed down the deuterosome motilities. In the presence of nocodazole, we captured 15 cells that initiated their deuterosome biogenesis during the imaging (Fig E and Movie EV2) and 16 cells that already contained deuterosomes from the beginning and showed increased numbers of their deuterosomes over time (Movie EV3).…”
Section: Resultsmentioning
confidence: 99%
“…This intracellular transport is mediated by molecular motors, like kinesins and dyneins on microtubule tracks, and myosins on actin filaments (Hirokawa, Niwa, & Tanaka, ). In neurons, long‐range transport is predominantly mediated by microtubule‐based motor proteins and short‐range transport is typically thought to occur on actin filaments (Barlan & Gelfand, ; Langford, ). Actin‐dependent transport can occur in the following ways (a) myosin‐dependent cargo transport along actin filaments (Arden, Puri, Au, Kendrick‐Jones, & Buss, ; DePina & Langford, ; Semenova et al, ), (b) force‐based propulsion of cargoes by actin polymerization (Boldogh et al, ; Merrifield et al, ; Welch, Iwamatsu, & Mitchison, ), and (c) actin flow mediated organellar movement (Solecki et al, ; Trivedi et al, ).…”
Section: Role Of Actin In Organellar Transport In Neuronsmentioning
confidence: 99%
“…A number of organelles, including mitochondria, melanophores, and peroxisomes are known to become tethered to microtubule tracks by regulatory proteins that are crucial for maintaining their cellular distribution (23,25,28,41,42). Such tethering not only helps localize organelles along extended cell regions (as in neurons) (27,41) but is also thought to facilitate interactions between multiple organelles by restricting their three-dimensional diffusion through the cytoplasm (28). In the case of hitchhiking cargos such as peroxisomes in Aspergillus and Ustilago, tethering to a microtubule has the potential to enhance the rate of hitchhiking initiation by eliminating the time spent out of reach of the microtubule-bound carrier organelles.…”
Section: Tethering To Microtubules Enhances the Rate Of Hitchhiking Imentioning
confidence: 99%
“…In some cell types, organelles such as peroxisomes and mitochondria have been observed to attach to microtubules when not being actively transported (23)(24)(25). Such tethering allows for regulated placement of organelles within the cell (25)(26)(27)(28). Tethering may also enhance the ability of cargo to interact with the transport machinery, increasing the rate of initiating active runs while restricting short-range diffusion (19).…”
Section: Introductionmentioning
confidence: 99%